Rancang Bangun Pembangkit Listrik Tenaga Surya Off-Grid dan On-Grid Sebagai Media Pembelajaran Mahasiswa - Jeffry Anggara; Hasbi Assiddiq S; Ahmad Rizal; Ahmad Padli (P3M Politeknik Negeri Cilacap, 2026)
This study examines the performance of solar photovoltaic (PV) systems with off-grid and on-grid configurations as practical learning media at Politeknik Kotabaru. The testing was conducted on AC loads with parameters including solar radiation intensity, voltage, current, and the power stored in the battery. Monocrystalline and polycrystalline solar panels were used to compare energy conversion efficiency. The results show that monocrystalline panels perform better than polycrystalline panels, with average differences in power and efficiency of 1,30 W and 0,50% in the off-grid system, and 1,11 W and 0,44% in the on-grid system. Solar radiation intensity significantly affects output power and conversion efficiency, with the highest power of 49,28 W obtained at the maximum radiation intensity of 1015 W/m². This study confirms that the PV system trainer can serve as an effective learning medium to enhance students’ competence in understanding the differences between off-grid and on-grid systems.